Examining the Role of Social Networking Fatigue toward Discontinuance Intention: The Multigroup Effects of Gender and Age. Issue 2 (2nd April 2020) - Adhikari, Kishalay; Panda, Rajeev Kumar
Abstract: As more people want to register a social media presence, ineluctably, this creates a huge amount of content online. Prior research highlights that excessive information on social networking platforms leads to a usage related behavior termed as "social networking fatigue (SNF)." The present research draws from two major theories in information systems research- limited capacity model (LCM) and unified theory of acceptance and use of technology (UTAUT), to effectively understand the under-explored phenomenon of social networking fatigue. Online questionnaires were used to gather empirical data from 327 social networking users, out of which 306 samples were included in the final analysis. Structural equation modeling (SEM) techniques were employed for assessing the hypothesized relationships. This research will offer newer insights for conceptual development and assist the social media experts to formulate strategies for content modification and user engagement.